Vitamin B12-Catalyzed Dicarbofunctionalization of Bromoalkenes Under Visible Light Irradiation - Smoleń, Sabina; Wincenciuk, Aleksandra; Drapała, Olga; Gryko, Dorota (Synthesis, 2020)
Vitamin B12 plays a crucial role in enzymatic transformations. This natural compound proved also useful as a catalyst in numerous organic reactions. Commercial availability and lower cost than precious metal complexes, make cobalamin an attractive candidate for a broader use as a benign Co-catalyst. Herein, the vitamin B12-catalyzed dicarbofuntionalization of bromoalkenes with electrophilic olefins is reported leading to substituted pyrrolidines and piperidines in decent yields after only 15 minutes under light irradiation.
Keywords: cobalt; vitamin B12; radical cyclization; Giese addition